Quantum Transport - Allaire, Grégoire. (Springer, 2017)
Periodic Homogenization and Effective Mass Theorems for the Schrödinger Equation -- Mathematical Properties of Quantum Evolution Equations -- Quantum Hydrodynamic and Diffusion Models Derived from the Entropy Principle -- Multiscale Computations for Flow and Transport in Heterogeneous Media.